BIBLIOMETRIC DIMENSION OF INNOVATION COMMUNICATION PRODUCTIVITY OF TATA INSTITUTE OF SOCIAL SCIENCES - M.M., Koganuramah; Mallikarjun, Angadi; B.S., Kademani (Malaysian Journal of Library and Information Science, 2002)
Bibliometric analysis of 663 papers published by the social scientists of Tata Institute of Social Sciences during 1990-2000 in diverse domains in the social sciences were analysed for authorship pattern and collaboration. The results indicate that the collaboration co-efficient of the 613 single-authored papers is 92.46 percent, followed by 6.33 percent (42 papers) two authored papers. Maximum collaboration coefficient (0.13) was found during 1996-1997. The most prolific authors were: Murli Desai, Sarthy Acharya, Lakshmi Lingam, I.U.B. Reddy, Kailash, Shalini Bharat, and Chhaya Datar, publishing between 20-38 papers each. The core journals publishing TISS papers were: Indian Journal of Social Work (98), Economic and Political Weekly (26), Perspective of Social work (7), and All India Institute of Local Self Government (5)